THE PROGNOSTIC VALUE OF PHARMACOLOGICAL AND GENETIC TESTING IN MEDICAL THERAPY OF AGE-RELATED MACULAR DEGENERATION - N. A. Bakunina; S. N. Shcherbo; L. N. Kolesnikova (Российский офтальмологический журнал)
The review presents the analysis and possible ways of solving the issues of treatment of age related macular degeneration (AMD) based on pharmacogenetic approaches. The AMD problem is relevant because of the growing number of resistant neovascular membranes, an increase in the number of older-age patients, and a large number of complications from frequently used anti VEGF therapy as described in the literature. According to literary data, currently the most probable genes whose polymorphisms can affect the metabolism of drugs used, and hence the tactics of AMD treatment are: 1) CFH gene [complement factor H, chromosome 1q32 locus)]; 2) IL-8 gene; 3) ARMS2 gene of increased sensitivity to AMD; 4) VEGF-A gene; 5) NR3C1 gene. The need for diagnostic pharmacogenetic panels to select targeted AMD therapy is discussed. For citation: Bakunina N.А., Shcherbo S.N., Kolesnikova L.N. The prognostic value of pharmacological and genetic testing in medical therapy of age-related macular degeneration. Russian ophthalmological journal. 2018; 11 (2): 58-61. doi: 10.21516/2072-0076-2018-11-2-58-61 (In Russian).